Character Building With High Integrity In Lectures For Iain Pontianak Students In The Digitalization Era - Wahab; Putri Nabila Ramadani; Hemafitria; Purniadi Putra (Lembaga Bale Literasi, 2026)
The world of education in today's digital era faces various challenges as well as new opportunities, especially in the process of building student character. The purpose of this study is to see how the lecture process at IAIN Pontianak can play a role in shaping the character of high integrity, as well as the supporting and inhibiting factors faced by students in the digital era. The influence of digitalization on academic behavior, the role of lecturers, and the condition of students' integrity character were investigated through a qualitative approach involving observation and literature study. The research findings revealed that the majority of students realize the importance of integrity. However, its implementation in academic life is still constrained by easy access to technology that triggers plagiarism and academic fraud. The role of lecturers in instilling integrity values through active dialog and role modeling is very influential in shaping student character. Character education integrated into the curriculum, especially in religion and ethics courses, plays an important role in increasing students' moral awareness. Therefore, there is a need for collaboration between technology and effective teaching methods so that students can develop digital integrity attitudes.